Ground water augmentation plan for a degraded western ghat terrain using remote sensing and GIS - SOORAJ KANNAN P. V; Dr. E. K Mathew (Guide) (Tavanur 2007 Department of Irrigation and Drainage Engineering)
Ground water augmentation plan for a degraded western ghat terrain using remote sensing and GIS
Ground water augmentation plan for a degraded western ghat terrain using remote sensing and GIS